Analisis Kecurangan Laporan Keuangan dalam Perspektif Fraud Hexagon Theory - Kaffah, Muhammad; Afriyenti, Mayar (Universitas Negeri Padang, 2024)
This study aims to examine the effect of financial stability, nature of industry, auditor changes, board of directors changes, number of CEO photos and government projects on financial statement fraud. This study uses quantitative methods to test the theory and analyze the relationship between variables. The population in this study were construction companies listed on the Indonesia Stock Exchange in 2019-2023. This study uses purposive sampling method, there are 16 companies over a 5-year period and produces 80 observation data. The analysis technique used in this research is logistic regression analysis. The results of research with logistic regression analysis show that the financial stability variable has a positive effect on financial statement fraud. While the variables of auditor change, change of directors, number of CEO photos and government projects have no effect on financial statement fraud.